Perbandingan Konsumsi Daya Listrik Pada Hard Disk Drive Dengan Solid State Drive - Febrian Mario; Fernando Iskandar; Meredita Susanty (JURNAL TEKNOLOGIA, 2021)
One of the hardware solutions used for access speed-related needs is to maximize storage functions by developing conventional storage technology or what we know as Hardisk Drives (HDD) to become Solid State Drives (SSD). Different from conventional HDD architectures with magnetic disks, SSD have a flash storage architecture where read / write speeds are significantly better. Furthermore, the research conducted experiments using the data analysis technique. This study will discuss comparisons relating to HDD to SSD on a server. The expected output is in the form of data containing an increase in electricity and an increase in performance obtained after replacing an HDD with an SSD.